Inactivation defects caused by myotonia-associated mutations in the sodium channel III-IV linker (The Rockefeller University Press, 1996)
Missense mutations in the skeletal muscle Na+ channel alpha subunit occur in several heritable forms of myotonia and periodic paralysis. Distinct phenotypes arise from mutations at two sites within the III-IV cytoplasmic loop: myotonia without weakness due to substitutions at glycine 1306, and myotonia plus weakness caused by a mutation at threonine 1313. Heterologous expression in HEK cells showed that substitutions at either site disrupted inactivation, as reflected by slower inactivation rates, shifts in steady-state inactivation, and larger persistent Na+ currents. For T1313M, however, the changes were an order of magnitude larger than any of three substitutions at G1306, and recovery from inactivation was hastened as well. Model simulations demonstrate that these functional difference have distinct phenotypic consequences. In particular, a large persistent Na+ current predisposes to paralysis due to depolarization-induced block of action potential generation.